Thanatomicrobiome and its Influence in Determination of Time Since Death: A Review - Thritha Prasadh; Harshita Tiwari; Tripti Bhatnagar; Neeharika Srivastava (Indian Journal of Forensic Medicine and Pathology, 2025)
The thanatomicrobiome (thanatos, Greek for death) is a relatively new term and is the study of the microbes colonizing the blood, lymph, internal organs and orifices after death. Forensic investigations depend heavily on the postmortem interval (PMI), which measures the amount of time since death. Conventional approaches to PMI estimation frequently depend on both macroscopic and microscopic alterations in cadavers, which can be inaccurate and subject to several influences. A promising approach for PMI estimate has surfaced in recent years: the thanatomicrobiome, which is the community of bacteria that remain in the human body after death. This study aims to investigate the thanatomicrobiome signatures present in various visceral samples collected postmortem and assess their potential for accurate PMI estimation. Using high-throughput sequencing methods like metagenomics, microbial communities from various visceral samples taken from cadavers at certain times after death can create reliable thanatomicrobiome signatures for PMI estimation, law enforcement organisations and forensic professionals may be able to more precisely ascertain the time of death. This could improve the precision and dependability of forensic investigations. This article ensures a future in the advance forensic microbiology as a tool for forensic casework and contributing to the broader field of forensic science